2015
DOI: 10.1111/jcmm.12709
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib prevents pressure overload‐induced cardiac hypertrophy and dysfunction by inhibiting inflammation, apoptosis and oxidative stress

Abstract: To explore the effects of celecoxib on pressure overload‐induced cardiac hypertrophy (CH), cardiac dysfunction and explore the possible protective mechanisms. We surgically created abdominal aortic constrictions (AAC) in rats to induce CH. Rats with CH symptoms at 4 weeks after surgery were treated with celecoxib [2 mg/100 g body‐weight(BW)] daily for either 2 or 4 weeks. Survival rate, blood pressure and cardiac function were evaluated after celecoxib treatment. Animals were killed, and cardiac tissue was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…Oxidative stress is important in the development and progression of diverse cardiac disorders, including cardiac fibrosis (14), hypertrophy (22), apoptosis (23), inflammation (24) and resultant heart failure (25,26). It has previously been demonstrated that ROS may modulate ECM remodeling by mediating CF function and stimulating collagen turnover (26).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is important in the development and progression of diverse cardiac disorders, including cardiac fibrosis (14), hypertrophy (22), apoptosis (23), inflammation (24) and resultant heart failure (25,26). It has previously been demonstrated that ROS may modulate ECM remodeling by mediating CF function and stimulating collagen turnover (26).…”
Section: Discussionmentioning
confidence: 99%
“…CH of mice was evaluated by three methods 42 , 46 : (1) measurement of LV mass; (2) calculating the relative heart weight; and (3) detecting the changes of CH markers. See supplementary methods for details.…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory response is one of the research hotspots in the pathogenesis of cardiac hypertrophy (26). Previous studies have demonstrated that the activation of the NF-κB signaling pathway is closely associated with the inflammatory response, and it has been reported that NF-κB is involved in vascular remodeling, apoptosis and oxidative stress (27)(28)(29)(30). In addition, previous studies have confirmed that Iso can cause cardiac hypertrophy by activating the NF-κB signaling pathway, while the inhibition of NF-κB activation can counteract Iso-induced hypertrophy (7,31).…”
Section: Pyrroloquinoline Quinone Attenuates Isoproterenol Hydrochlormentioning
confidence: 99%